Investigation of Chitosan Grafting and Uptake Properties of Some Metal Ions by Atomic Absorption Spectrophotometry - Temuz, Mehmet Mursit; Cataldas, Emrullah (Taylor & Francis Inc, 2024)
In the research described here, to graft chitosan with the atom transfer radical polymerization (ATRP) method, chitosan acetyl chloride was obtained as a macro-initiator by reacting chitosan with chloracetyl chloride. This macro-initiator was then grafted with monomer [acrylamide (AM) or methacrylamide (MAM), or diacetone acrylamide (DAAM)] in the presence of 2,2'-bipyridine/CuCl as a catalyst system. Structure characterization of all synthesized products was performed with the help of elemental analysis and IR techniques. Additionally, the metal ions (Cu2+, Co2+, Ni2+, and Cd2+) uptake properties of the polymers were determined by atomic absorption spectrophotometry. Metal ion uptake parameters were calculated using various formulas and the results were compared.
Keywords: atom transfer radical polymerization; chitosan; graft copolymer; metal uptake